Potensi Wakaf sebagai Investasi Sosial Masyarakat di Indonesia - Hanum Faradia; Habsiyah Asyidah (Al Mabhats : Jurnal Penelitian Sosial Agama, 2024)
Abstract: In the context of Islamic law, waqf is defined as a legal act involving the dedication of property by an individual to a person or institution, whereby the property is to be used for charitable purposes, with the core asset being permanent in nature. This concept offers greater flexibility compared to zakat, allowing waqf to evolve in response to contemporary needs while adhering to sharia principles. It is essential that the development of waqf remains within the bounds of sharia to uphold the values of ubudiyah (servitude to God) and iqtishadiyah (economic welfare). Indonesia possesses significant potential for waqf land; however, a considerable portion remains unproductive due to challenges related to funding and management. In response, the Indonesian government introduced sukuk-based waqf innovations in early 2017 to optimize the utilization of waqf land. Nevertheless, the legal framework surrounding sukuk remains a subject of scholarly debate and is characterized by differing opinions within Islamic jurisprudence. To effectively implement sukuk-based waqf, it is crucial to establish clear regulatory frameworks this financial innovation. Additionally, attention must be given to the proper administration of waqf assets, including land and building certificates, as well as waqf certificates. Ensuring compliance with sharia legality is paramount, as it allows the fundamental objectives of waqf to serve the community and enhance social welfare to be achieved without compromising the integrity or value of the waqf assets.